Sulphur removal from Artvin-Yusufeli lignite with acidic hydrogen peroxide solutions - Levent, Menderes; Ö, Kaya; Kocakerim M.M.; Ö, Küçük (Inderscience Publishers, 2016)
In this study, the optimisation of sulphur removal by H2O2/H2SO4 solutions, and a limited kinetic measurements by H2O2/HCl solutions have been carried over Artvin/Yusufeli lignite. In kinetic measurements, only the effect of temperature on removal of sulphur has been investigated. By keeping all other parameters constant, with increments in temperature at different times, it has been seen that removal of sulphur is increased. A statistical experimental arrangement which has six parameters and for each parameter there is twenty five experiments with five levels. In generally, pyritic sulphur, total sulphur, organic sulphur and ash removal rates have been determined. According to carried out variance analysis, in removal of pyritic and total sulphur, all parameters are effective, but, in removal of organic sulphur, acid concentration and particle size are not effective, and in removal of ash, only, acid concentration is not effective, however, all other parameters are effective.
Keywords: Desulphurisation; Pyritic sulphur; Lignite; Organic sulphur; Hydrogen peroxide; Total sulphur; 3. Good health